STUDI KEBERADAAN SENYAWA BIOAKTIF IMUNOSUPRESAN PADA EKSTRAK TESTIS SAPI BALI (Bos sondaicus) MELALUI UJI IN VITRO - Primawati, Sri Nopita (Bioscientist : Jurnal Ilmiah Biologi, 2018)
A study of the existence of Bioactive Immunosuppressant Compounds on Balinese Testis Extract (Bos sondaicus) through In Vitro Test. This study aims to study the provision of bioactive compounds immunosuppressant that has been extracted from cow testes against inhibition of lymphocyte cell ploriferation. The effects of these immunosuppressant compounds can be observed from ploriferation of Mus musculus lymphocytes cells to injections (exposure) of Bali Cow Testicular Extract exposed together or without concanavalin A (Con A, as a trigger for lymphocyte cell proliferation) and Bovine Serum Albumin (BSA) as standard solution . This research was designed with Completely Randomized Design (RAL). The data obtained were analyzed by ANOVA analysis using F-test. The results of this study indicate that injection of Balinese Cervical Test Extract exposed simultaneously with BSA (ET + BSA) can increase the proliferation of Balb / c lymphocyte cell culture in In Vitro (p <0.05) compared with control and exposure of BSA and Con A together for 72 hours. However, when exposed without Con A and BSA, the Bali Cattle Testicular Extract significantly suppressed (immunosuppressed) lymphocyte cell proliferation (p <0.05) compared with exposure to Con A.